The role of a translator and translation in business communication - Tsaryk, Olga; Mariana, Sokol; Rybina, Nataliia; Smyła, Joanna (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The work concerns the role of the translator as a mediator for intercultural communication in its connection with the theory of translation, paying special attention to the latter as one of the main means of communication. The authors have also revealed the essence of the concept of “intercultural communication” and have considered the place and significance of translation as its direct tool in its structure in general and in the process of business communication in particular.